2016
DOI: 10.1161/circulationaha.116.024790
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin G Controls Arterial But Not Venular Myeloid Cell Recruitment

Abstract: BACKGROUND Therapeutic targeting of arterial leukocyte recruitment in the context of atherosclerosis has been disappointing in clinical studies. Reasons for such failures include the lack of knowledge of arterial-specific recruitment patterns. Here we establish the importance of the cathepsin G (CatG) in the context of arterial myeloid cell recruitment. METHODS Intravital microscopy of the carotid artery, the jugular vein, and cremasteric arterioles and venules in Apoe−/− and CatG-deficient mice (Apoe−/−Ctsg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 46 publications
(52 reference statements)
3
56
0
Order By: Relevance
“…These chemokines, such as CCL5, CXCL1, and CCL2, can be produced either by endothelial cells or by subendothelial macrophages, neutrophils, and monocytes [20, 21]. In addition, activated leukocytes release granular proteins, such as CRAMP, MPO, and cathepsin G, which can bind to the endothelium and attract leukocytes [22, 23]. …”
Section: Mechanisms Of Arterial Leukocyte Entrymentioning
confidence: 99%
See 1 more Smart Citation
“…These chemokines, such as CCL5, CXCL1, and CCL2, can be produced either by endothelial cells or by subendothelial macrophages, neutrophils, and monocytes [20, 21]. In addition, activated leukocytes release granular proteins, such as CRAMP, MPO, and cathepsin G, which can bind to the endothelium and attract leukocytes [22, 23]. …”
Section: Mechanisms Of Arterial Leukocyte Entrymentioning
confidence: 99%
“…In agreement with this, also other studies have highlighted the importance of the platelet-neutrophil interaction in monocyte recruitment during the initial phase of atherosclerosis. Besides heteromer formation of platelet-derived CCL5 with neutrophil HNP-1, CCL5 also activates neutrophils to release cathepsin G, which binds to endothelium and fosters monocyte adhesion [23]. Hypercholesterolemia-induced neutrophilia is positively correlated with the extent of early lesion development, while neutropenic mice have fewer lesional inflammatory monocytes and macrophages [20].…”
Section: Mechanisms Of Arterial Leukocyte Entrymentioning
confidence: 99%
“…In this context, a recent study has identified the importance of cathepsin G during arterial myeloid cell recruitment, a mechanism of minor relevance during microvascular myeloid cell adhesion. Accordingly, neutralization of cathepsin G in mouse models did not affect neutrophil extravasation during acute lung inflammation but instead specifically limited atherogenic leucocyte recruitment . Secondly, disruption of protein heteromers formed by neutrophil and platelet secretory products efficiently reduces myeloid cell adhesion.…”
Section: Means Of Therapeutic Intervention—from Bench To Bedside?mentioning
confidence: 97%
“…First, in a sequential cooperativity, platelets activated by high‐shear forces secrete CCL5 which is deposited on arterial endothelial cells. Interestingly, the deposition of CCL5 predominantly at sites of high‐shear forces initiates a recruitment mechanism restricted to large arteries . CCL5 promotes the release of cathepsin G from neutrophils which in turn is laid onto arterial endothelial cells.…”
Section: Platelet‐neutrophil Cooperativity During Monocyte Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation